Effect of Neem (Azadirachta indica) and other Plant Extracts on Yellow Mite of Jute - Hossain, M. D.; Yasmin, S.; Latif, M. A.; Akhter, N. (International Journal of Bio-resource and Stress Management, 2013)
A field experiment was conducted to evaluate the effectiveness of neem and some other plant extracts against yellow mite of jute, Polyphagotarsonemus latus (Banks), at the Jute Agriculture Experimental Station (JAES), Manikgonj, Bangladesh during the period from April to August, 2008. Green and dry neem leaf, neem oil, turmeric powder, garlic, mahagoni seed and green allamonda leaf were tested against the pest. Among the different plant materials, neem oil showed the best performance and reduced 64.37%, 84.75% and 93.47% yellow mite population over control after 24, 48 and 72 hours of spraying respectively. The percent plant infestation was also found lowest in neem oil treatment. The treatment had the lowest percent of leaf infestation 4.99%, 3.80% and 0.53% and also the highest reduction of no of nodes per plant 44.39%, 52.4% and 43.85% over control at early, mid and late stages of jute plant respectively. Neem oil increased 24.64% plant height, 27.87% base diameter over control and gave the highest amount of fibre yield (2.68 t ha-1). Green and dry neem leaf extracts, turmeric powder and garlic paste also significantly reduced the mite infestation but their efficacy was not satisfactory. Neem oil and mahagoni seed extract might be used for the control of yellow mite but it needs to explore the toxic compound of mahagoni seed.